2003
DOI: 10.1074/jbc.m305108200
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Prostaglandin E2 Production by Membrane-bound Prostaglandin E Synthase-2 via Both Cyclooxygenases-1 and -2

Abstract: Current evidence suggests that two forms of prostaglandin (PG) E synthase (PGES), cytosolic PGES and membrane-bound PGES (mPGES) -1, preferentially lie downstream of cyclooxygenase (COX) -1 and -2, respectively, in the PGE 2 biosynthetic pathway. In this study, we examined the expression and functional aspects of the third PGES enzyme, mPGES-2, in mammalian cells and tissues. mPGES-2 was synthesized as a Golgi membrane-associated protein, and spontaneous cleavage of the N-terminal hydrophobic domain led to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
310
3
8

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(340 citation statements)
references
References 65 publications
19
310
3
8
Order By: Relevance
“…In contrast, no major changes in COX-1 expression were noted in either cell type. PGE 2 is the major prostaglandin generated in the skin and is produced by the action of the microsomal PGE 2 synthases, mPGES-1 and mPGES-2 (Murakami et al, 2003). We found that mRNA expression of these enzymes increased 4-6-fold in both undifferentiated and differentiated keratinocytes following exposure to UVB (Fig 6).…”
Section: Effects Of Uvb On Expression Of Coxs Prostaglandin Synthasmentioning
confidence: 69%
“…In contrast, no major changes in COX-1 expression were noted in either cell type. PGE 2 is the major prostaglandin generated in the skin and is produced by the action of the microsomal PGE 2 synthases, mPGES-1 and mPGES-2 (Murakami et al, 2003). We found that mRNA expression of these enzymes increased 4-6-fold in both undifferentiated and differentiated keratinocytes following exposure to UVB (Fig 6).…”
Section: Effects Of Uvb On Expression Of Coxs Prostaglandin Synthasmentioning
confidence: 69%
“…35 PGES1 is involved in the COX-2-mediated PGE2-biosynthetic pathway 35 ; mPGES2 is abundant in brain, heart, skeletal muscle, kidney, and liver 37 ; cPGES is distributed ubiquitously in the cytosol of various cells 36 ; and COX-1 contributes to PGE2 generation by PGES2 and cPGES. 36,39,40 We immunohistochemically confirmed the presence of mPGES1 in primary basophils, but we were unable to assess the protein expression of the other PGES enzymes, because antibodies against mPGES2 and cPGES were not available in our laboratory. Nevertheless, transcripts encoding mPGES1, mPGES2, and cPGES were all detected in BMBAs.…”
Section: Discussionmentioning
confidence: 96%
“…Microsomal PGES-1 is induced by proinflammatory agents and is down-regulated by glucocorticoids in various cells (3,5,6). In contrast to the inducible mPGES-1, another mPGES (mPGES-2) is constitutively expressed in many cells without any further induction during inflammation (7). In addition, a cytosolic protein possessing PGES activity (cPGES) has been characterized and found to be constitutively expressed in various cells (8).…”
mentioning
confidence: 99%
“…It has been demonstrated that mPGES-1 functionally uses PGH 2 generated by COX-2 (5,6), but some evidence also exists for a role of COX-1 (9). Recently, it has been shown that synoviocytes isolated from patients with RA coexpress both mPGES-1 and COX-2 and generate high amounts of PGE 2 after treatment with proinflammatory cytokines (10); mPGES-1 expression has also been detected in RA synovial lining cells (7).…”
mentioning
confidence: 99%